Sounds of the game: An interpersonal discourse analysis of 'on field' language in sports media. (March 2020) - Caldwell, David
Highlights: Interpersonal discourse analysis of unmapped new media sports discourse: on-field language tracking texts. Construction of heuristic taxonomy for language tracking texts according to their interpersonal language features. Examination of solidarity and power between on-field players, and between audience and language tracking text. Examination of language tracking text as site for future mediatization research. Abstract: The new media representation of 'on-field' sports discourse presents an exciting opportunity for social linguists to engage with an uncharted, pervasive and mediatized discourse. This paper begins by introducing on-field language tracking and briefly reviewing the research in sports mediatization and the application of linguistics to sports discourse. Drawing on the applied social-linguistics theory of Systemic Functional Linguistics (Martin and Rose, 2007), with mediatisation as a second-order investigation (Livingstone and Lunt, 2014), the paper examines a range of examples of on-field language tracking from several professional sports including basketball, cricket, and Australian football. An interpersonal discourse semantic analysis (Martin and White, 2005) is applied to the data, with the aim to bring to consciousness the ways in which players construe solidarity and power through language with each other, as well as audience. The results and discussion reveal the emergence of three distinct on-field 'stances' – the communing, the condemning and the instructing. The paper then concludes in a more speculative mode, considering key future directions, particularly language tracking in sports mediatization research.